Discussing motherhood when the oncological prognosis is dire: ethical considerations for physicians. Issue 6 (10th November 2020) - Linkeviciute, Alma; Buonomo, Barbara; Fazio, Nicola; Spada, Francesca; Peccatori, Fedro A
Abstract : Physicians are increasingly open to discussing and supporting pregnancy after cancer treatment. However, counselling patients who are seeking pregnancy despite advanced oncological disease and/or uncertain prognosis is still challenging. Two paradigmatic cases are presented and analysed to illustrate the ethical uneasiness faced by treating physicians when seriously ill patients seek fertility preservation and/or pregnancy. Review of ethical issues is built around the four principles of biomedical ethics. Respect for patients autonomy in relation to managing realistic expectations and avoiding giving patients false hopes opens the analysis. It is followed by considering fair allocation of resources and meaningful distinction between protecting patients from harm and contributing to their welfare. Responsibilities towards the unborn child are discussed in a light of maternal and fetal interdependency. Respecting personal autonomy requires abstaining from controlling inferences to the individual patient's choices, but it does not mean that patients should be left on their own to pick and choose their disease management approaches without advice and guidance from healthcare professionals. Physicians should reason evaluating the potential harms and checking if benefits will outweigh the risks and if costs will produce the best overall results. Responsibilities towards the unborn child can be managed by balancing the respect for maternal autonomy and beneficence for pregnant woman and her fetus. The oncologist cannot determine how patients should view their disease but with empathy and compassion can help them understand the logical rationale behind clinical advice.